Community service program (PkM): sharia financial literacy education for teachers at Mizanul Ulum Islamic Boarding School, Takalar - Darmawangsa, Andi; Surani; Akil, Muhammad; Ardi (Universitas Ahmad Dahlan, 2023)
The education of Sharia financial literacy is becoming increasingly important in the context of pesantren (Islamic boarding schools) in Indonesia as an effort to strengthen the understanding of teachers about the principles of Sharia finance and how to apply them in daily life. In Pesantren Mizanul Ulum Sanrobone Takalar, attention to Sharia financial literacy education requires special consideration. This Community Service Program (PkM) aims to explore a community service program conducted to enhance the understanding of teachers in the pesantren regarding Sharia financial literacy. The research method used is a combination of observation, interviews, and the distribution of questionnaires to teachers in the pesantren. The research results indicate an urgent need for a better understanding of Sharia financial concepts and how to apply them in daily life. The implemented PkM program successfully improved the understanding of teachers regarding Sharia financial literacy and increased their confidence in viewing finances from a Sharia perspective.